Effect of Reward Types and Forms of Punishment on Student Learning Interest in Islamic Cultural History Subjects in Class VII MTs N III Boyolali - Rosidah, Anisa; Wibowo, Ari (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The problem in this study is that most students still talk to their peers and even do other activities outside of SKI learning. The purpose of this study has three objectives, namely to (1) determine the effect of reward types on SKI learning interest in grade VII students at MTs N 3 Boyolali, (2) knowing the effect of punishment forms on SKI learning interest in class VII students at MTs N 3 Boyolali, (3) knowing the interaction between reward types and punishment forms in influencing SKI learning interest in class VII students at MTs N 3 Boyolali. The research method used is a quantitative method of experimentation. The place of this research was conducted at MTs Negeri 3 Boyolali. The time of the study starts from January 2018 until January 2019. Data collection uses a questionnaire method filled by 150 students and observation in class. The results of the validity and validity test use the product moment formula. Test the reliability of the interest in learning using the split technique. The data analysis test uses mean, median, mode, standard deviation and line box diagrams. Hypothesis testing uses two-way anava. The results showed that (1) there was an effect of the type of reward on SKI learning interest in grade VII students at MTs N 3 Boyolali with sig. equal to 0,000, (2) there is an influence of the form of punishment on the interest in learning SKI in class VII students at MTs N 3 Boyolali with sig. equal to 0,000, (3) there is no interaction between the types of rewards and forms of punishment in influencing the interest in learning SKI at the level of 5%, while at the level of 10% there is an interaction between the types of rewards and forms of punishment in influencing the interest in learning of SKI grade VII students at MTs N 3 Boyolali with sig. amounted to 0.073. The explanation for the interaction is as follows: punishment form of reprimand if combined with reward rewards and praise can increase students' interest in learning SKI, as well as punishment of logical consequences combined with reward rewards. However, if the reward of praise is combined with the logical consequences of student interest in learning SKI is low. So it can be concluded that if punishment punishment is combined with reward rewards and praise then students' interest in learning is high, so is the logical consequence punishment combined with reward rewards. However, if the reward of praise is combined with the logical consequences of punishment, students' interest in learning SKI is low.